1993
DOI: 10.1037/0022-006x.61.3.434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training in time-limited dynamic psychotherapy: Changes in therapist behavior.

Abstract: Sixteen therapists were enrolled in a year-long manualized training program as part of the Vanderbilt II study of time-limited dynamic psychotherapy (TLDP). The training program successfully changed therapists' interventions in line with prescriptions of the TLDP manual, but some unanticipated changes ran counter to the intent of the training, including increased negative interpersonal transactions as indicated by process measures such as the Structural Analysis of Social Behavior (SASB). We examined therapist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
305
2
6

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(333 citation statements)
references
References 15 publications
19
305
2
6
Order By: Relevance
“…Prior research has shown that therapists with certain self-hostile introjects engage in greater frequencies of countertherapeutic interpersonal process, such as complex communication (Henry, Schacht, & Strupp, 1990). In our earlier article (Henry, Strupp, Butler, Schacht, & Binder, 1993), we reported a significant increase in complex communications at the group level after training. Accordingly, we wanted to explore whether the posttraining increase in complex communications was caused by a subset of therapists based on introject quadrant.…”
Section: Tural Analysis Of Social Behavior (Sasb) and The Vanderbilt mentioning
confidence: 80%
See 2 more Smart Citations
“…Prior research has shown that therapists with certain self-hostile introjects engage in greater frequencies of countertherapeutic interpersonal process, such as complex communication (Henry, Schacht, & Strupp, 1990). In our earlier article (Henry, Strupp, Butler, Schacht, & Binder, 1993), we reported a significant increase in complex communications at the group level after training. Accordingly, we wanted to explore whether the posttraining increase in complex communications was caused by a subset of therapists based on introject quadrant.…”
Section: Tural Analysis Of Social Behavior (Sasb) and The Vanderbilt mentioning
confidence: 80%
“…A number of therapist behaviors in different domains were measured preand posttraining, with therapists serving as their own controls. Thus, the design focused on the effects of training in a single treatment manual rather than comparing the differential outcome efficacy of several competing protocol therapies.Analyses of therapist changes at the group level revealed both intended and unintended results (Henry, Strupp, Butler, Schacht, & Binder, 1993). The training program successfully changed therapists' technical interventions in line with prescriptions in the TLDP manual.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Although the merit in common practitioner concerns about manualized approaches (Addis, Wade, & Hatgis, 1999) may be questioned (Fonagy, 1999), the empirical literature indicates that treatment manuals do not ensure effective delivery of therapy (Binder, 1993;. However, based on a small number of studies that produced conflicting results, and given the limitations of study methodology, it is less clear whether that which is gained in adherence to specific techniques through manuals (CritsChristoph et al, 1998;Henry, Strupp, Butler, Schacht, & Binder, 1993;Hilsenroth, Defife, Blagys, & Ackerman, 2006;Multon et al, 1996) may be at the expense of other therapeutic factors and therapeutic progress (Strupp & Anderson, 1997).…”
Section: Treatment Manuals In Psychodynamic Psychotherapymentioning
confidence: 99%
“…For example, Henry, Strupp, Butler, Schacht, and Binder (1993) found that overly conscientious adherence to the treatment manual in the Vanderbilt II study led shortterm psychodynamic therapists to achieve less favorable results. A comparable finding is reported by Castonguay, Goldfried, Wiser, Raue, and Hayes (1996) with cognitive therapists, whereby strict adherence to the manual was associated with difficulties in the therapeutic alliance.…”
Section: Use Of Treatment Manualsmentioning
confidence: 99%